Universal Neonatal Hearing Screening: An Experience at Tertiary Care Hospital - Shrestha, B.L.; Karmacharya, S.; Dhakal, A.; KC, A.K.; Shrestha, K.S.; Pradhan, A.; Rajbhandari, P.; Pokharel, M. (Kathmandu University Medical Journal, 2020)
Background Hearing loss among neonates is one of the important health issue in pediatric population which may remain unnoticed until the child reaches a certain age. The importance of universal early screening, diagnosis and intervention in reducing the negative impact of congenital hearing loss has been described all over the world. Objective To observe the outcome of hearing screening by Automated Auditory Brainstem Response (AABR) in newborns delivered in Dhulikhel Hospital and neonates admitted in an intensive care unit (NICU) of Dhulikhel Hospital. Method A prospective study was done in neonates who were born at Dhulikhel Hospital, Kathmandu University Hospital from February 15th, 2017 to October 30th, 2019. AABR was used for their hearing assessment within 24 hours of birth and again at about 6 weeks of age in those neonates who failed the initial test. All the neonates admitted in NICU were studied regarding the risk factors based on Joint committee on Infant Hearing. Those who failed the test for the second time were referred for detailed audiological diagnostic work up. Result The screening rate was 92.6% of the total deliveries. A total of 5517 neonates comprising of 2800 males and 2717 females were screened from total deliveries of 5956 neonates in the study period. Among them, NICU (sick) babies were 422 (7.7%) and well babies were 5095 (92.3%). Out of them, 1675 failed the test in the first screening and 374 failed in the second screening. So, the total number of referred babies in second screening was 6.7% (374) out of 5517 screened. Amongst them, well babies were 6.59% (336), out of 5095 screened and sick babies were 9% (38) out of 422 screened. Low birth weight and prematurity were found to be the commonest risk factor present among them, followed by the use of ototoxic medications, hyperbilirubinemia and prolonged use of mechanical ventilation. Conclusion Automated Auditory Brainstem Response (AABR) is a very useful tool for hearing screening which should preferably be done in all the neonates where possible. It should be done within one month of life and those with confirmed hearing loss should receive early appropriate intervention for better hearing in future.